Personality and sport experience of 20-29-year-old Polish male professional athletes - Piepiora, P.; Piepiora, Z.; Bagiñska, J. (Frontiers in Psychology, 2022)
More and more research reports assert that sport experience has an influence on shaping the personality of athletes. This paper aims at validating the connection between personality and sport experience. The research subject of were young Polish male athletes (N = 1,260) aged 20-29, out of 42 sports disciplines, with sport experience ranging from 3 to 12 years. In order to test the personality of the research subjects, a five-factor model of personality called the Big Five was applied. Statistical calculations and analyses were carried out with ver. 25 of the IBM SPSS Statistics software. The research has shown that all personality traits correlate in a statistically significant way with sport experience (p < 0.001): there is a negative correlation of sports experience with neuroticism and a positive correlation with traits such as extraversion, openness to experience, agreeableness, and conscientiousness. Thus, we have identified a relationship between sport experience and personality traits of the researched Polish male athletes—the longer the sport experience, the lower level of neuroticism and higher levels of extraversion, openness to experience, agreeableness, and conscientiousness. Duration of sport experience has a considerable influence on forming the personality of Polish male athletes. However, the interpretation of just the results regarding high level of extraversion and conscientiousness distinguishes Polish male athletes (20-29 years old) from the Polish male population of non-training people.